When Security Overrules Reason: McCarthyism in View of The Cases of Charles Chaplin and Lucille Ball - Erzsébet Árvay (Diacronie. Studi di Storia Contemporanea, 2016)
Counter-Intelligence operations as part of modern warfare serve the purpose of national security. However, these operations often target civilians, and therefore give rise to serious allegations which can have devastating effects on many people’s life. The aim of this paper is to depict the mechanisms of the McCarthy era in view of the persecution of Charles Chaplin and Lucille Ball. Their cases aptly illustrate the controversial tactics and methods of McCarthyism in post-war America. To explore the networks used by authorities and actors of anti-communist operations, this paper exploits the archival sources of Chaplin’s and Ball’s cases which adds up to over two thousands pages in the records of the MI5 and the FBI. The fully detailed records give an insight into the impact of espionage accusations on civilians’ lives and provide a good account of post-war American intelligence actions.